EFL PEER FEEDBACK THROUGH THE CHATROOM IN PADLET - Sari, Angela Bayu Pertama (English Education Study Programme of Sanata Dharma University, Yogyakarta, Indonesia, 2019)
This research was conducted to achieve two objectives. The first one is to give a vivid explanation about the peer feedback practice through Padlet chatroom. Secondly, it was carried out to dig out the students’ responses toward that practice. It was conducted within qualitative descriptive research by employing observation and open-ended questionnaires of 70 non-English university students as its data collecting technique. Then, qualitative data analysis was utilized by the researcher. The results revealed Padlet usage is a new thing for most of the students, yet they can use it easily because it is user-friendly and cost-free. Moreover, anonymity becomes one of the prominent features in Padlet chatroom. The students found it more convenient as being anonymous in giving and receiving feedback due to the freedom of expressing the students’ feedback without worrying about their friends’ sense of emotion. The last finding showed that the peer feedback practice through Padlet chatroom had met five principles out of seven principles that are proposed as the basic requirements of feedback practices. DOI: doi.org/10.24071/llt.2019.220105